1996
DOI: 10.1128/aac.40.9.2111
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sparfloxacin and autoradiographic diffusion pattern of [14C]Sparfloxacin in experimental Staphylococcus aureus joint prosthesis infection

Abstract: Using a new rabbit model of methicillin-susceptible Staphylococcus aureus knee prosthesis infection, we compared the efficacies of sparfloxacin (50 mg/kg of body weight subcutaneously, twice a day) and pefloxacin (50 mg/kg subcutaneously, twice a day). A partial knee replacement was performed with a silicone implant fitted into the intramedullary canal of the tibia, and 5 x 10(7) CFU of methicillin-susceptible S. aureus was injected into the knee. The 7-day treatment regimen was started 15 days later. The MICs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Another preventive approach relying on a minocycline/rifampin-impregnated bioresorbable polymer implant coating has been shown to reduce biofilm formation [ 289 ]. Another key contribution of these models is the study of distribution and efficacy of frequently used antibiotics such as fluoroquinolones [ 290 ].…”
Section: In Vivo Models Of Device-related Infecmentioning
confidence: 99%
“…Another preventive approach relying on a minocycline/rifampin-impregnated bioresorbable polymer implant coating has been shown to reduce biofilm formation [ 289 ]. Another key contribution of these models is the study of distribution and efficacy of frequently used antibiotics such as fluoroquinolones [ 290 ].…”
Section: In Vivo Models Of Device-related Infecmentioning
confidence: 99%
“…Such a minimal detection limit is a relative drawback of all studies that evaluate implantrelated infections using a comparable plating and counting technique. 22,[38][39][40][41][42][43][44][45] However, many studies do not mention the minimal detectable level of bacteria. Early experiments have shown that, in the presence of a foreign body, a number of 100 CFU of a staphylococcal strain is enough to produce an infection in man.…”
Section: Discussionmentioning
confidence: 99%
“…Radiolabeled antibodies performed poorer compared to autologous leukocyte scintigraphy (accuracy ranging from 75-86%), while no data on the use of [ 18 F]FDG-PET and PET/CT in primary appendicular osteomyelitis are available (exect for chronic, see below) [10]. Tc-ciprofloxacin (Infecton TM , a radiolabeled broad-spectrum fluoroquinolone that inhibits the DNA-gyrase and/or 8 topoisomerase IV of bacteria) have been used in pediatrics patients with clinical suspicion of osteomyelitis (98% sensitivity and 100% specificity, with a 100% positive predictive value and a 87% negative predictive [22]) despite the low specificity for osteoarticular infections (aspecific accumulation in growth plates, non-infected prosthetic knees, pseudoarthrosis, palindromic rheumatism, and postoperative fibrosis of the lumbar spine, avascular hip necrosis, fibrous dysplasia, non-union fracture, and uninfected prosthetic joints [23][24][25][26][27][28] (those resultshad also been reported in animal model with another radiolabeled quinolone, 14 C-sparfloxacin [29]). Preliminary results of 68 Ga-citrate PET/CT compared to different combinations of diagnostic procedures (MRI, radiography, CT, or labeled WBC scintigraphy), biopsy (when diagnostic), and follow-up data (at least 1 year), have been reported in 31 patients with suspected osteomyelitis or diskitis.…”
Section: Bone Infections 211 Peripheral Bone Osteomyelitismentioning
confidence: 99%
“…Additionally, 99m Tc-ciprofloxacin results at the end of therapy had the highest sensitivity (83%), accuracy (70%) and negative predictive value (95%) in predicting infection resolution or recurrence as compared to ESR assessment and clinical examinations [155]. UBI [29][30][31][32][33][34][35][36][37][38][39][40][41] was also employed to differentiate infection from aseptic loosening of prostheses [156] as well as to assess response to antibiotic therapy with reduction in radiopharmaceutical uptake after treatment as compared to baseline scan in the responder group [157].…”
Section: Prosthetic Joint Infectionsmentioning
confidence: 99%
See 1 more Smart Citation